Effect of Chemical and Radiochemical Impurities from Eluants on 99mTc-Labeling Efficiency - Colombetti, L. G.; Earl Barnes, W. (Nuklearmedizin - NuclearMedicine, 1977)
Occasionally, radiopharmaceuticals prepared from the eluates of 99Mo-99m T c generators that have not been eluted for several days contain large amounts of free pertechnetate, as tested by radiochromatography and biologically by administration to patients. We find the most probable causes of poor 99mTc-labeling in these cases to be:a) the presence of a large concentration of 99TcO4– in eluants;b) insufficient stannous ions available for the complete reduction of Tc due to spontaneous oxidation of Sn in the vial and also due to oxidation of stannous ions by the presence of larger than expected concentrations of H2O2 and HO2 radicals in the eluant.